2013
DOI: 10.1371/journal.pone.0065146
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Left Atrial Function Using a Multi-Scale Model of the Cardiovascular System

Abstract: During a full cardiac cycle, the left atrium successively behaves as a reservoir, a conduit and a pump. This complex behavior makes it unrealistic to apply the time-varying elastance theory to characterize the left atrium, first, because this theory has known limitations, and second, because it is still uncertain whether the load independence hypothesis holds. In this study, we aim to bypass this uncertainty by relying on another kind of mathematical model of the cardiac chambers. In the present work, we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Even severe stenosis caused only a slight decrease in cardiac output although the mean systolic pressure gradient between LV and aorta achieved 50 mmHg. The good match of the results of the simulation with clinical recommendations showed that simple Equations (11) to (13) for pressure drop across the valve provided a reasonable quantitative fit of major integral hydrodynamic characteristics of complicated nonsteady blood flow through a stenotic aortic valve.…”
Section: Effects Of Valve Diseases On Heart Performancementioning
confidence: 77%
See 1 more Smart Citation
“…Even severe stenosis caused only a slight decrease in cardiac output although the mean systolic pressure gradient between LV and aorta achieved 50 mmHg. The good match of the results of the simulation with clinical recommendations showed that simple Equations (11) to (13) for pressure drop across the valve provided a reasonable quantitative fit of major integral hydrodynamic characteristics of complicated nonsteady blood flow through a stenotic aortic valve.…”
Section: Effects Of Valve Diseases On Heart Performancementioning
confidence: 77%
“…This model was used to simulate normal circulation and acute or chronic pulmonary hypertension. Pironet and colleagues suggested multiscale models in that 0D multiscale models of the LV, alone or combined with a model of the left atrium, were based on a sarcomere model . Using these models, they simulated the dependence of the end‐systolic pressure‐volume relations on preload and afterload, mitral valve resistance, etc., and estimated the contribution of the left atrium to the LV function.…”
Section: Introductionmentioning
confidence: 99%
“…where, P LV (t), V(t), and V 0 are the LV time-varying pressure, time-varying volume, and unloaded volume, respectively (Keshavarz-Motamed et al, 2016). As explained by Keshavarz-Motamed (2020), to represent the normalized elastance function of the LV, we observed that among summation of Gaussian functions (Pironet et al, 2013;Chaudhry, 2015), Boltzmann Distribution (McDowell, 1999), double Hill function (Mynard et al, 2012;Broomé et al, 2013), and the latter provided the most physiologically accurate results (e.g., pressure, volume, and flow waveforms). The double Hill function which is a cooperative process (Moss et al, 2004), as physiologically expected from myocyte recruitment during preload and is modeled by a sigmoidal Hill function.…”
Section: Left Ventriclementioning
confidence: 94%
“…It has not yet been shown that the time varying elastance theory can be applied to the atria as it is done to the ventricle. Other authors have developed alternate methods to represent the atria such as the multi-scale model [26]. However, the large number of parameters required for such methods to work cannot be identified using the limited data clinically available, making it unsuitable to apply in this work.…”
Section: Limitationsmentioning
confidence: 99%